Farm Broadcasting--The First Sixty Years; Agri Marketing; "Public Service Utilization by Texas Radio Stations"; "Enjoyment and information Gain in Science Articles"; "Choose the right color for your Learning Style."; Instant Speaking Course - Richard Lee; Delmar Hatesohl; Randy Weckman; Annette Sanders; Joe Marks (Journal of Applied Communications, 1981)
Reviews of Farm Broadcasting--The First Sixty Years, by John C. Baker ; Agri Marketing; "Public Service Utilization by Texas Radio Stations," by W. Bryant Boutwell; "Enjoyment and information Gain in Science Articles," by Alan Hunsaker; "Choose the Right Color for Your Learning Style," by Esther R. Sinofsky and Frederick G. Knirk; Instant Speaking Course, by B. Lauren Lillis.